Notas sobre a biologia reprodutiva e alimentar de elasmobrânquios no Parque Estadual Marinho Parcel Manoel Luís, Maranhão - Brasil - Motta, Fabio S. [UNESP]; Moura, Rodrigo L.; Francini-Filho, Ronaldo B.; Namora, Rafael C. [UNESP] (My University, 2009)
Data on the reproductive and feeding biology of elasmobranchs from Manoel Luís Reefs, Maranhão State, Brazil. Nine species were recorded and evidences that the area is important for the reproduction and feeding activity of sharks and rays were obtained.
Keywords: Feeding habits; Marine protected areas; Rays; Reproduction; Sharks; Chondrichthyes; Elasmobranchii